2018
DOI: 10.1155/2018/5950739
|View full text |Cite
|
Sign up to set email alerts
|

Professional Learning and Development of Postdoctoral Scholars: A Systematic Review of the Literature

Abstract: Increasing numbers of postdoctoral scholars are pursuing diverse career paths that require broad skill sets to ensure success. However, most postdoctoral professional learning and development initiatives are designed for academic careers and rarely include professional skills needed to flourish in nonacademic settings. The purpose of this systematic review was to comprehensively examine and synthesize evidence of professional learning and development pertaining to postdoctoral scholars. The systematic search r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 54 publications
0
22
0
Order By: Relevance
“…Two extensive literature reviews were completed. The first examined and synthesized evidence of postdoc PLD (Nowell et al, 2018). The second synthesized the literature that described current approaches to PLD for postdocs (Nowell et al, 2019).…”
Section: Evidence Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Two extensive literature reviews were completed. The first examined and synthesized evidence of postdoc PLD (Nowell et al, 2018). The second synthesized the literature that described current approaches to PLD for postdocs (Nowell et al, 2019).…”
Section: Evidence Synthesismentioning
confidence: 99%
“…Existing PLD opportunities for postdocs may not be robust, but the global need for postdocs to develop skills for various career trajectories is clear (Nowell et al, 2018;Nowell et al, 2019). Rigorous evaluation of the impact of and investment in PLD for postdocs is needed.…”
Section: Future Researchmentioning
confidence: 99%
“…A number of studies have identified postdoctoral fellows' desires for opportunities to develop teaching and learning skills (Nowell et al, 2018). Often, professional development opportunities are designed to support research-focused careers, with little thought given to broader professional skills (Mitchell et al, 2013).…”
Section: Program Administration: Inclusion Of Postdoctoral Fellowsmentioning
confidence: 99%
“…While emphasis has been placed largely on research skill development, engaging in a range of professional learning and development activities may increase postdocs' knowledge, skills, abilities, and growth while improving their performance in present or future positions (Åkerlind, 2005;Webster-Wright, 2009). In a recently published systematic review, the authors determined professional learning and development positively impacted postdocs' teaching and learning skills, writing and publication skills, and general career skills (Nowell et al, 2018). Other outcomes of engaging in professional learning and development included developing a community of peers with other postdocs, enhancing work-life balance, and purposefully planning for professional learning and development (Nowell et al, 2018).…”
mentioning
confidence: 99%
“…In a recently published systematic review, the authors determined professional learning and development positively impacted postdocs' teaching and learning skills, writing and publication skills, and general career skills (Nowell et al, 2018). Other outcomes of engaging in professional learning and development included developing a community of peers with other postdocs, enhancing work-life balance, and purposefully planning for professional learning and development (Nowell et al, 2018). The authors conducted a further literature review and identified common goals for professional learning and development initiatives for postdocs were to develop teaching and learning, mentorship, academic writing, networking, and communication skills (Nowell et al, 2020).…”
mentioning
confidence: 99%